Spinocerebellar ataxia type 8 in Scotland: genetic and clinical features in seven unrelated cases and a review of published reports. Issue 3 (13th February 2004) - Zeman, A; Stone, J; Porteous, M; Burns, E; Barron, L; Warner, J
Abstract : Objectives: To establish whether the DNA expansion linked to spinocerebellar ataxia type 8 (SCA 8) is associated with ataxia in Scotland; to clarify the range of associated clinical phenotypes; and to compare the findings with previous reports. Methods: DNA was screened from 1190 anonymised controls, 137 subjects who had tested negative for Huntington's disease, 176 with schizophrenia, and 173 with undiagnosed ataxia. Five unrelated ataxic patients with the SCA 8 expansion and a sixth identified subsequently had clinical and psychometric assessment; the clinical features were available in a seventh. A systematic search for other reports of SCA 8 was undertaken. Results: Over 98% of SCA 8 CTA/CTG repeat lengths fell between 14 and 40. Repeat lengths over 91 were observed in three healthy controls (0.12%), two patients with suspected Huntington's disease (0.73%), and six ataxic subjects (1.74%; p<0.0005 v healthy controls). Repeat lengths over 100 occurred in five ataxic subjects but in only one control. All seven symptomatic subjects with the SCA 8 expansion had a cerebellar syndrome; four had upper motor neurone signs; and 5/6 assessed had cognitive complaints. There was personality change in two and mood disturbance in three. In published reports, SCA 8 repeat lengths over 91 occurred in ~0.5% of the healthy population but were over-represented among ataxic patients (3.4%; p<0.0001). The predominant clinical phenotype was cerebellar, with pyramidal signs in 50%, and neuropsychiatric features in some cases. Conclusions: SCA 8 expansion is a risk factor for a cerebellar syndrome, often associated with upper motor neurone and neuropsychiatric features. The expansion occurs unexpectedly often in the general population.